The athletic performance of elite rugby league players is improved after an 8-week small-sided game training intervention - Seitz, L. B.; Rivière, M.; de Villarreal, E. S.; Haff, G. G. (The Journal of Strength and Conditioning Research, 2014)
The purpose of this investigation was to determine the effects of a small-sided game training intervention on the intermittent shuttle running performance, speed, and repeated sprint ability of elite rugby league players during the competitive phase of a rugby league season. Ten elite rugby league players from a Stobart Super League team academy underwent 2 small-sided game sessions per week over an 8-week period. Each session consisted of four 10-minute blocks of 1 small-sided game, interspersed with a 3-minute recovery. Changes in physical performance were assessed before and after the training intervention with an intermittent shuttle running test (30-15 Intermittent Fitness Test), speed tests (10-, 20-, and 40-m linear sprints) and a repeated sprint ability test (8 × 20-m linear sprint, departing every 20 seconds). Results showed that the 30-15 Intermittent Fitness Test (+1.29%), 10-m (-3.17%), 20-m (-1.37%), and 40-m (-0.96%) sprint times and mean sprint time (-2.11%), total sprint time (-2.11%), and percentage of sprint decrement (7.10 vs. 5.93%) during the repeated sprint ability test were significantly improved after the training intervention. Based on these results, it was concluded that an 8-week small-sided game training intervention was an effective method for improving the physical performance of elite rugby league players during the competitive phase of the season.